Պատճառականությունը և քրեաիրավականության հանրային ընկալումները - Ռաֆիկ Սանթրոսյան (ՀՀ ԳԱԱ հրատ.)
В данной статье предпринята попытка выявить связь между каузативностью и восприятием обществом понятия "право". Особое внимание уделяется лексическим единицам, выражающим "лишение жизни" в английском и армянском языках. This paper tries to bring out the link between the scope of the causality factor and public perception of the criminal law. Especially, the lexical units conveying the notion of "deprivation of life" expressions in both English and Armenian languages are thoroughly investigated.
Keywords: Law; Philology; Linguistics; Criminal Law